2020
DOI: 10.1101/2020.04.01.019851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design and power analysis for multi-sample single cell genomics experiments

Abstract: Background:The identification of genes associated with specific experimental conditions, genotypes or phenotypes through differential expression analysis has long been the cornerstone of transcriptomic analysis. Single cell RNA-seq is revolutionizing transcriptomics and is enabling interindividual differential gene expression analysis and identification of genetic variants associated with gene expression, so called expression quantitative trait loci at cell-type resolution. Current methods for power analysis a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 93 publications
(133 reference statements)
0
10
0
Order By: Relevance
“…We performed a prospective analysis of presbyosmic or control normosmic subjects, to obtain nasal mucosal biopsies for analysis. No statistical method was used to predetermine sample size; rather, we have followed current best practices for scRNA-seq studies, and, guided by goals for rare cell type identification, expected read depth, and identification of DE genes for specific clusters, utilized three subjects in each cohort (61). Tissue samples from a single patient were processed individually; as was a single cell culture sample for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a prospective analysis of presbyosmic or control normosmic subjects, to obtain nasal mucosal biopsies for analysis. No statistical method was used to predetermine sample size; rather, we have followed current best practices for scRNA-seq studies, and, guided by goals for rare cell type identification, expected read depth, and identification of DE genes for specific clusters, utilized three subjects in each cohort (61). Tissue samples from a single patient were processed individually; as was a single cell culture sample for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a prospective analysis of presbyosmic or control normosmic subjects, to obtain nasal mucosal biopsies for analysis. No statistical method was used to predetermine sample size; rather, we have followed current best practices for scRNA-seq studies, and, guided by goals for rare cell type identification, expected read depth, and identification of DE genes for specific clusters, utilized three subjects in each cohort (45). Tissue samples from a single patient were processed individually.…”
Section: Methodsmentioning
confidence: 99%
“…For example, based on the user-specified frequency of the rarest cell population and the number of populations with approximately this frequency, SCOPIT (Davis et al 2019) can estimate the number of cells for planning single-cell sequencing experiments. Schmid et al (2020) developed scPower, a more general framework for single-cell power calculation, in which they showed that, for a fixed budget, the number of cells per individual is the major determinant of power of detecting rare cell types and differentially expressed genes, followed by the number of subjects and read depth. In general, shallow sequencing of high numbers of cells per individual leads to a higher overall power than does deep sequencing of fewer cells.…”
Section: Number Of Cells and Sequencing Depth Per Cellmentioning
confidence: 99%